MAKNA SIMBOL BUDAYA ORGANISASI PT. POS INDONESIA DALAM MENGHADAPI PERSAINGAN PELAYANAN DI KOTA PEKANBARU - Dina Pitria; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The symbol is a representation for a review of Meaning. Members of the organization and creates, using and interpreting symbols everyday. The symbols include verbal and non verbal communication that is in hearts as well as the organization. Often time the singer communicates symbols organization and Values. The extent to which the symbols Effective singer, depends not only on media, but how members organization and practice in PT. Pos Indonesia (Persero) UPT Pekanbaru. Singer study aims to review identify cultural symbols as well as the organizational form of physical symbol, a symbol of Behavior, verbal symbols and knowing the employees' understanding Against these symbols in PT. Pos Indonesia (Persero) Pekanbaru UPT hearts Faced with competition. Singer Research using qualitative research method is descriptive and is backed with Organizational Culture Theory. On Subject Research singer is determined by purposive sampling technique consists Over The Human Resources Manager, Company employees and society. The data collection techniques include interviews, observation and documentation. Mechanical Analysis using Interactive Data Model Miles and Huberman with checks the validity of data is done using the extension of participation and triangulation techniques. Research shows that employees' understanding against symbols of organizational culture as well Namely symbol Physical Form slogan logo games, clothing and building has understood with Good And a Reference Values Underlying their hearts work, while the symbol of Conduct is that the rewards and punishments is with benchmark because their employee rewards, employees are motivated to review the findings of the Best leave so that organizational goals can be achieved as well as Maximum Operating. Symbol oral anekadot states, Jokes And the funny stories and more impressive familiarity make with the others so that employees feel the absence of jatropha too far with other employees and hearts Faced with competition Also the ministry PT. Pos Indonesia UPT Pekanbaru strive to provide the Best hearts pelayananannya shown to 'public order' community services using with differences interpret symbols the in PT. Pos Indonesia UPT. Pekanbaru.Keywords: physical symbol, behavior symbol, verbal symbol